2020
DOI: 10.35911/torani.v3i1.6813
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Zooplankton Abundance with Phytoplankton and Physic-Chemistry Parameters at Kastela Waters, Ternate

Abstract: Zooplankton has an important role in waters, especially in the food chain, these organisms are consumers I which play a major role in bridging energy transfer from major producers (phytoplankton) to living things at higher trophic levels (fish and shrimp). This study aims to analyze the relationship between zooplankton abundance with phytoplankton and physicochemical parameters in the waters of Kastela, Ternate. The research was conducted from March to April 2017 in the waters of Kastela Ternate City North Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Our results showed that the diversity indices ranged 2,04 to 2,32. According to Yuliana et al (2012), the index value of diversity 1<H'<3 described a moderate level of diversity with medium ecological stress. According to Basmi (2000), the condition of moderate community is a condition which can readily change even though the change of its environment is not relatively significant.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the diversity indices ranged 2,04 to 2,32. According to Yuliana et al (2012), the index value of diversity 1<H'<3 described a moderate level of diversity with medium ecological stress. According to Basmi (2000), the condition of moderate community is a condition which can readily change even though the change of its environment is not relatively significant.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ability of oxidation, the determination of the value of COD is considered to be the best in describing the presence of organic matter, 20 whether or not biologically decomposed. [21][22][23][24]…”
Section: Based On Ri Regulation No 82 Of 2001 Concerning River Watermentioning
confidence: 99%